Systematic Review: Improving Body Immunity through Consumption of Vitamins in Facing COVID-19 - Kiki Puspitasary; Meliana Novitasari; Rina Tri Handayani; Siti Maesaroh; Lilik Hanifah; Ani Nur Fauziah (Journal for Quality in Public Health, 2022)
COVID-19 was declared an international pandemic after it was first reported in 2019 in Wuhan, China and caused a public emergency not only in Indonesia but throughout the world. Efforts to prevent the transmission of the COVID-19 virus are very important because there is still no specific drug to deal with COVID-19. The healing of a person with COVID-19 is strongly influenced by the body's immunity, including by consuming vitamins B, C, D, E and Zinc. The purpose of this study was to find out how to increase the body's immune system through the consumption of vitamins in the face of the COVID-19 pandemic. The design of this study uses a systematic review, namely library research that examines critically quality health journals, which have been filtered with inclusion criteria and uses several databases of Google Scholar, Pubmed, Science Direct and Research Gate as literacy in this study. There are 350 journals according to keywords which are filtered into 7 journals according to the theme and analyzed which examines increasing the body's immunity with vitamin B, C, D, E and Zinc supplementation. The results showed that the potential of vitamins to increase the body's immunity in the prevention of COVID-19.